NILAI â€“ NILAI PERTEMANAN YANG DICERMINKAN DALAM NOVEL WHITE TEETH KARYA ZADIE SMITH - LAOH, REYNALT JUNIOR; WAROUW, MAYA PINKAN; PAMANTUNG, RINA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTWhite Teeth is a 2000 novel by the British author Zadie Smith. It focuses on the later lives of two wartime friends the Bangladeshi Samad Iqbal and the Englishman Archie Jones and their families in London.This research Entitledâ€Nilai-nilai pertemanan yang dicerminkan dalam Novel White Teeth Karya Zadie Smithâ€ aims to find the values of friendship that exist in the novel through the nature of some of the characters in the novel. this research is expected to be useful for readers in order to understanding the meaning of friendship in life.Through the Friendship Theories by James O.Grunebaum and characterby Robert Stanton, the data were collected by emphasizing on the process and the factors that affected the characters in friendship in the story. In analyzing the data, the writer used the descriptive method with extrinsic and intrinsic approach.The results show that the friendship values of the author are determines the values of friendship and also the value of friendship shown in the characterization of Zadie Smith's White Teeth novel which is illustrated by two main characters, Archie Jones and Samad Iqbal, including the Value of Understanding, Trust, Loyalty and Cooperation as stated above has an influence on their lives and their survival after World War II.Keyword: Friendship Values, Characters, Zadie Smith, White Teeth